(untitled) (Bangladesh Journal of Agricultural Research, 2009)
Legume leaves used as green manure are a potential alternative to commercial fertilizers for non-legume crop production. Therefore, many researches have been conducted to understand the pattern of legume leaf decomposition and its release of nutrients. A study on Gliricidia leaves decomposition was conducted under laboratory conditions to elucidate the effect of grinding size of Gliricidia leaves (S1 = ≤ 0.5 mm, S2 = 4 mm, and S3 = 9 mm) on microbial respiration and N mineralization after incorporation in to the soil. The early stages of the incubation were found to be significantly influenced by the particle size of the Gliricidia leaves. Particle size S2 (4 mm) was reported to exhibit the highest C and NH4+-N mineralization. However, in the case of NO3+-N mineralization, no treatment was found to be significant. It could thus be hypothesized that physical protection of finely ground (< 0.5 mm) Gliricidia leaves was responsible for the relatively low rates of decomposition. Key Words: Decomposition, mineralization, Gliricidia leaves. DOI: 10.3329/bjar.v34i3.3957 Bangladesh J. Agril. Res. 34(3) : 343-350, September 2009